FOUNDING ENVIRONMENTAL AWARENESS AT NURUL ASNA ISLAMIC BOARDING SCHOOL - Ismawati, Tri (Journal of Islam and Science, 2018)
Islamic boarding school has types of environments. They are dirty environment and clean environment. In this case it needs activity to create Islamic boarding school that has clean and health environment. This study discussing the form of environmental awareness coaching in the Nurul Asna Islamic boarding school. This study used qualitative approach with the technique of collecting data through observation, and interview so that the conclusion was found: 1) create coaching awareness about clean environment at Islamic boarding school Nurul Asna that guided by headmaster and teacher, and the activity was create schedule cleanliness, community service two times in a month, and give cleanliness slogan. 2) the aim of coaching awareness about environment at Islamic boarding school Nurul Asna was: create cleanliness environment, student was more discipline and better than before, familiarize their selve to love the environment, and to prevent from various diseases especially skin diseases that usually suffered by studen. 3) Student has run a method of fostering environmental awareness that has been made. This is evidenced by the santri having maintained cleanliness by removing garbage, doing pickets according to the schedule and participating in the implementation of routine activities in two weeks.